Artifical Synapses: Synaptic Plasticity and Filtering Emulated in Metal–Organic Frameworks Nanosheets Based Transistors (Adv. Electron. Mater. 1/2020). (13th January 2020) - Ding, Guanglong; Yang, Baidong; Zhou, Kui; Zhang, Chen; Wang, Yaxin; Yang, Jia‐Qin; Han, Su‐Ting; Zhai, Yongbiao; Roy, Vellaisamy A. L.; Zhou, Ye
Abstract : In article number 1900978, Su‐Ting Han, Vellaisamy A. L. Roy, Ye Zhou, and co‐workers demonstrate a three‐terminal synaptic transistor based on MOF materials. This device exhibits ambipolar charge‐trapping performance and can simulate biological synaptic behaviors, enabling the realization of learning functions and signal transmission simultaneously.